Percutaneous Device to Narrow the Coronary Sinus: Shifting Paradigm in the Treatment of Refractory Angina? A Review of the Literature - Benedetto, Daniela; Abawi, Masieh; Stella, Pieter R.; Nijhoff, Freek; Lakemeier, Maxime D. M.; Kortlandt, Friso; Doevendans, Pieter A.; Agostoni, Pierfrancesco (Frontiers in Cardiovascular Medicine, 2016)
Refractory angina pectoris is defined as a chronic debilitating condition characterized by the presence of chronic anginal symptoms due to a severe obstructive and/or diffuse coronary artery disease that cannot be controlled by the combination of medical therapy and / or revascularization (percutaneous or surgical). In addition the presence of myocardial ischemia as a cause of the symptoms must have been documented. The coronary sinus Reducer (CSR) is a recently introduced percutaneous device to treat patients with severe anginal symptoms refractory to optimal medical therapy and not amenable to conventional revascularization. The purpose of this review is to describe the current evidence from available studies measuring the clinical effect of the CSR implantation on the health and well-being of patients with refractory angina.